Insights from the compositional evolution of a multi-coloured, zoned tourmaline from the Cruzeiro pegmatite, Minas Gerais, Brazil - G. B. Andreozzi; G. B. Andreozzi; C. Gori; H. Skogby; U. Hålenius; A. Altieri; F. Bosi; F. Bosi (European Journal of Mineralogy)
This study compares the compositional evolution of a multi-coloured, zoned tourmaline crystal from the Cruzeiro pegmatite, Brazil, with the compositions of homogeneous tourmaline crystals systematically collected from the outer to the inner zones of the same pegmatite. Four representative fragments of the multi-coloured, zoned tourmaline were thoroughly investigated using single-crystal X-ray diffraction; electron microprobe analysis; and 57Fe Mössbauer, Fourier transform infrared, and optical absorption spectroscopies to obtain the full composition and site occupancies. The fragments are classified, from core to rim, as WO-rich, F-bearing schorl (black inner and outer core) and Fe2+-rich, WOH-bearing fluor-elbaite (blue inner and green outer rim). A negative correlation between F and Fe2+ contents was evidenced, approximated by the equation F = 1 − 0.33Fe2+ (in atoms per formula unit) and consistent with the observed tourmaline evolution from schorl to fluor-elbaite.